"A Biometeorological Time Scale for Cereal Crop Involving Day and Night Temperatures and Photoperiod" by George W. Robertson, International Journal of Biometeorology (1968) 12:191–223. Issue 6 (6th September 2018) - Sinclair, Thomas R.
Abstract : This article is part of a series of brief commentaries to highlight papers that have resulted in important and distinctly new perspectives in crop science. A criterion for the selection of papers is that they must have been published at least 20 yr ago to allow for a long‐range perspective in assessment of the papers. The current article briefly reviews the paper by George Robertson published in 1968 that provided key concepts used yet today to describe the pace of plant development. Robertson developed the ideas of normalized development rates for each ontogenetic stage, multiplication of temperature and photoperiod responses, and inclusion of base temperature and photoperiod parameters in the response functions.